Ventilation performance of solar chimney in a test house: Field measurement and validation of plume model. (15th April 2021) - He, Guoqing; Wu, Qian; Li, Zhengguang; Ge, Wenqing; Lv, Da; Cong, Lei
Abstract: The potential of solar chimney in building ventilation has long been recognized. However, very few data have been reported on its ventilation performance in actual buildings. In this study, the field performance of a solar chimney attached to a test house was studied under Hangzhou climate conditions. The ventilation rates were determined by measuring the airflow rate in the chimney channel. The results show that the solar chimney provided relatively consistent air changing rates of about 2–5 h −1 on average 24 h a day despite that it was installed on the south-east wall. With the wind influence suppressed using a windproof net at the chimney outlet, the solar radiation and the temperature difference between the room and the outside were two major sources contributing to the stack flow. The inverse condition, higher room temperature than the outside, was the major driving force of stack flow during the absence of solar radiation. The limiting effect of the room inlet size was also demonstrated. The field data validated the plume model, which predicted all the data with reasonable accuracy. Our study indicates that a properly designed solar chimney can provide reliable ventilation round the clock during most time of the year in Hangzhou or cities with similar climate. Extra measures are only needed in summer times when neither the solar radiation nor the inverse condition is available.